2013
DOI: 10.4172/2167-7689.1000108
|View full text |Cite
|
Sign up to set email alerts
|

Micellar Solubilization in the Formulation Development of Poorly Soluble Naproxen

Abstract: The aim of this study was to improve the dissolution rate of naproxen using micellar solubilization technology. Cloud point temperature of the nonionic surfactants has been used as the basis for the solubility study because there is better entrapment of the drug into the surfactant micelle at this temperature. Naproxen was solubilized in polysorbate 80 micelles at cloud point temperature; lactose was dissolved in micellar dispersion and the dispersion was directly spray-dried to obtain microparticles, which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…As previously reported [ 40 , 56 ], the cloud point of a system is influenced by the inter-micellar interactions of the polymers, and the physicochemical characteristic of the mixed micelles may substantially differ from that of single micelles. Soluplus has a cloud point of 40.7 ± 0.8 °C (Mean ± SD, n = 3) [ 40 ], while Solutol ® HS15 of 70.0 ± 0.7 °C (Mean ± SD, n = 3) [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…As previously reported [ 40 , 56 ], the cloud point of a system is influenced by the inter-micellar interactions of the polymers, and the physicochemical characteristic of the mixed micelles may substantially differ from that of single micelles. Soluplus has a cloud point of 40.7 ± 0.8 °C (Mean ± SD, n = 3) [ 40 ], while Solutol ® HS15 of 70.0 ± 0.7 °C (Mean ± SD, n = 3) [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…5 ) was also used to investigate a specific transformation from crystalline naproxen to an amorphous structure following solid dispersion generation. In SDN-2 and SDN-5, a new (agglomerated) morphology different from pure naproxen crystalline structure was identified, which improved water retention and therefore increased naproxen's dissolution rate [ 38 ], suggesting that the pure drug naproxen was mixed well with carriers PEG-8000 and Na starch glycolate devoid of phase separation and appeared as amorphous nature. In a prior study, in contrast [ 39 ] with pure naproxen powder, which had the appearance of flat flakes, the morphology of the PVP-infused naproxen significantly changed and grew dendritically, which was in charge of improving the solubility and dissolving rate of pure naproxen.…”
Section: Resultsmentioning
confidence: 99%
“…These microparticles were converted into tablets using suitable excipients. It was found that the dissolution rate was higher in all the dissolution media irrespective of the pH conditions in both spraydried naproxen particles and directly compressed tablets [72].…”
Section: Literature Reviewed On Microparticles Entrapped Micellesmentioning
confidence: 96%